Critical insurance studies: Some geographic directions. (October 2021) - Booth, Kate
Critical insurance studies recognises insurance as not purely actuarial and calculative. From this recognition, this theoretically informed research pays attention to the reproduction of power in insurantial discourse and practice, and possibilities for equitable change. To extend geographical contributions in this regard, I review critical insurance research and describe three intersecting foci – governmentality, materiality and spatiality. I also contribute new insights in considering insurance as co-constituting fluid and fire space – as flowing and adapting within everyday complexities, and as fiery and constituted through multiple flickering realities. These contestable multiplicities and mobilities may contribute to more equitable configurations beyond the hegemonic.